2019
DOI: 10.1126/science.aar7785
|View full text |Cite
|
Sign up to set email alerts
|

The human gut bacterial genotoxin colibactin alkylates DNA

Abstract: Certain Escherichia coli strains residing in the human gut produce colibactin, a small-molecule genotoxin implicated in colorectal cancer pathogenesis. However, colibactin’s chemical structure and the molecular mechanism underlying its genotoxic effects have remained unknown for more than a decade. Here we combine an untargeted DNA adductomics approach with chemical synthesis to identify and characterize a covalent DNA modification from human cell lines treated with colibactin-producing E. coli. Our data estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
399
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(419 citation statements)
references
References 42 publications
16
399
0
4
Order By: Relevance
“…Our results were in agreement with previous studies performed in CAC‐related models showing that CoPEC oncogenic properties are not restricted to their persistence site . In the first publication describing the in vitro colibactin effect, it was suggested that direct contact between bacteria and target‐cells was required to induce double‐strand DNA breaks and genomic instability . However, other studies have already described a bystander effect of CoPEC through the induction of cellular senescence in infected cells and the production of growth factors that could promote the proliferation of uninfected cells and, subsequently, tumor growth .…”
Section: Discussionsupporting
confidence: 92%
“…Our results were in agreement with previous studies performed in CAC‐related models showing that CoPEC oncogenic properties are not restricted to their persistence site . In the first publication describing the in vitro colibactin effect, it was suggested that direct contact between bacteria and target‐cells was required to induce double‐strand DNA breaks and genomic instability . However, other studies have already described a bystander effect of CoPEC through the induction of cellular senescence in infected cells and the production of growth factors that could promote the proliferation of uninfected cells and, subsequently, tumor growth .…”
Section: Discussionsupporting
confidence: 92%
“…Consequently,t he reactive cyclopropanol ring of the malleicyprols represents an important pharmacophoric moiety.Aprominent example with as imilarly strained warhead substructure is the genotoxin colibactin. [17] In conclusion, we have discovered and characterized an ew family of structurally intriguing, cyclopropanol-substituted polyketides.I ng eneral, cyclopropanol-containing natural products are exceedingly rare. [16,18] We demonstrate that these highly reactive compounds are produced by the bur/mal assembly line,w hich is correlated with virulence in the B. mallei/pseudomallei complex, and suggest alternative polyketide virulence determinants.T hus,o ur results are an important addition to the body of knowledge on smallmolecule disease mediators employed by these infamous human and animal pathogens.T his new insight may lead to abetter understanding of the molecular basis of glanders and melioidosis,a nd could facilitate the development of much needed therapeutics [19] to combat these severe diseases.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…However, it has not been fully elucidated whether changes in the intestinal microbiota are a cause or a result of carcinogenesis, or whether the microbiota contributes to cancer progression. Some gut bacteria produce genotoxic metabolites: for example, a few species of the genus Clostridium produce deoxycholic acid (DCA) and pks + E coli strains produce colibactin . Current knowledge on the potential links between diet and intestinal residues as a trophic resource for the gut microbiota and carcinogenesis is only fragmental.…”
Section: Introductionmentioning
confidence: 99%
“…Some gut bacteria produce genotoxic metabolites: for example, a few species of the genus Clostridium produce deoxycholic acid (DCA) 12 and pks + E coli strains produce colibactin. 13 Current knowledge on the potential links between diet and intestinal residues as a trophic resource for the gut microbiota and carcinogenesis is only fragmental. To address this issue, we established a large human cohort study in Japan, in which we collected fecal samples and a food frequency questionnaire from the same subjects and conducted multi-omics analyses to comprehensively study dietary habits and metagenome and metabolome data in relation to CRC.…”
mentioning
confidence: 99%